Falsafah Maqasid al-Quran Imam al-Ghazali dan faham ilmu - Siddig Ahmad,; Wan Suhaimi Wan Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
One of the internal problems faced by Muslims today is confusion and mistakes in understanding the meaning, hierarchy, and scope of the limitations of knowledge. As a result, there is a collapse of manners, which refers to the loss of physical discipline, mind and soul that demands identification and recognition of the right place for a person in his relationship with himself and his society. Islam does not concede to the dichotomy of al-dunya and al-akhirah aspect. The worldview of Islam encompasses both al-dunya and al-akhirah in which the al-akhirah aspect has ultimate and final significance. The al-dunya aspect is seen as a preparation for the al-akhirah aspect. Everything in Islam is ultimately focused on the al-akhirah aspect without thereby implying any attitude of neglect or being unmindful of the al-dunya aspect. Knowledge that reveals the mysteries of Existence and reveals the true relationship between man and his God that is closely related to the main purpose of human creation is the main basis and foundation for other knowledge. This is because other knowledge itself, without the guidance of this main basic knowledge, will not be able to guide people correctly in their lives and will only confuse and ensnare people into an endless search. This article will cover the main basis of knowledge based on the understanding of knowledge derived from the philosophy of maqasid al-Qur'an presented by Imam al-Ghazali through his book Jawahir al-Qur'an.